Antioxidant Potential of Yellow Chrysanthemum (Chrysanthemum indicum) Leaves: In Vitro Analysis Using DPPH and FRAP Techniques - Gabriella Therezia Ley Ley; Billy Johnson Kepel; Fatimawali Fatimawali; Aaltje Ellen Manampiring; Fona Dwiana Hermina Budiarso; Widdhi Bodhi (Graha Primera Saintifika, 2025)
The shift from infectious diseases to non-communicable diseases (NCDs), driven by aging and unhealthy lifestyles, has led to an increase in degenerative diseases. The World Health Organization (WHO) reported that NCDs account for 74% of global deaths. An imbalance between free radicals and antioxidants contributes to the progression of these diseases, highlighting the need for research on plant-derived antioxidants. Secondary metabolites, particularly phenolic and flavonoid compounds, are abundant in Chrysanthemum indicum and are known for their potential antioxidant properties. This study aims to identify the secondary metabolites and evaluate the antioxidant activity of yellow chrysanthemum (Chrysanthemum indicum) leaves using two methods: Ferric Reducing Antioxidant Power (FRAP) and 2,2-diphenyl-1-picrylhydrazyl (DPPH). The extraction process was performed using the reflux method with 96% ethanol as the solvent. Antioxidant activity was assessed using the DPPH and FRAP methods, with absorbance measurements conducted via UV-Vis spectrophotometry. Phytochemical screening revealed the presence of phenols, flavonoids, tannins, steroids/triterpenoids, and alkaloids in the ethanol extract of yellow chrysanthemum leaves. The antioxidant activity assay using the DPPH method indicated a value of 64.34 ppm, signifying strong antioxidant activity. In contrast, the FRAP method showed weak antioxidant activity, with an IC50 value of 187.13 ppm.